GreenScenario. A collaborative software-based decision-support tool and integrated planning process for climate-conscious and evidence-based design. - Anterola, Jeremy Karl (Technische Hochschule Ostwestfalen-Lippe, IDS Institut für Designstrategien, 2021)
In dem Beitrag wird das kollaborative und software-basiertes Entscheidungstool GreenScenario vorgestellt. Integrierte digitale Planungsprozesse für Konzepte zur wassersensiblen und klimaangepassten Stadtentwicklung erlangen eine immer größere Bedeutung in Stadtplanung und Architektur. „GreenScenario“ ist eine softwarebasierte Planungsleistung des Büros Ramboll Studio Dreiseitl, welche Kommunen und Projektentwickler:innen unterstützt, um informierte Entscheidungen zur klimaangepassten Planung anhand von datengesteuerten Ergebnissen zu treffen. GreenScenario wird angewendet um in iterativen Schritten Planungsvarianten zu simulieren, zu testen und zu optimieren.

GreenScenario was developed as a software-based decision support tool to break down and transform the complexity of climate adaptation into an understandable and useful form of information, most especially for those involved in the decision-making process for masterplanning and city development (e.g. municipalities, property developers, relevant stakeholders). Key learnings from the application of GreenScenario in practice suggest that in order to increase acceptance of data-driven software methods as part of the design development process, decision-support tools must be able to deliver results rapidly, visually and in a practical, easy-to-understand manner. Humans have a limited ability to think and visualise long-term i.e. beyond 15 to 20 years; geospatial visualisations (e.g. images) of complex data enable humans to process complex information. Thus, solutions need to be contextually specific and integrated in locally established community planning processes (Schroth, Pond, Sheppard, 2015). A potential solution combining these observations and gaining acceptance as a method within climate change adaptation planning is the application of ‘Scenario Planning’ as a decision-support process that combines a rigorous, scientific assessment within the framework of multiple scenario (solution) generation (Star et al, 2016). Computational design techniques as they relate to developing digital decision-support systems or platforms, while found to be practical and implementable at building and plot scales, were found to be particularly challenging to apply at urban, regional and city scales due to increased computational expense, difficulty in limiting inputs, and the increase in involved stakeholders involved in the planning process (Wilson et al, 2019). By describing the findings of multiple projects where the GreenScenario methodology has been applied within the context of European cities with a specific focus on its use by a property developer in Vienna, the results aid in identifying enablers and barriers for the use and acceptance of decision-support tools for climate change adaptation planning.
Keywords: Masterplan; Nachhaltige Stadtentwicklung; EDV-Software; Entwurfsparameter; Evaluation; Nachhaltiges Bauen; Mikroklima; Hitzebelastung